Secondary school girls’ knowledge and practice on human papillomavirus (HPV), cervical cancer and human papillomavirus (HPV) vaccination in Kuantan, Pahang, Malaysia - Aung, Khin Thandar; Md Merzuki, Nurul Syafiqa; Zaw, Cho Cho (2017)
Background: Cervical cancer becomes the second leading cancer in Malaysia and HPV infection is the main cause of this cancer. The availability of HPV vaccination can reduce down the risk of getting HPV infection thus will also reduce incidence of cervical cancer. However, due to little current information pertaining to the nature of HPV infection, cervical cancer and HPV vaccination themselves among the risky age, which is secondary school girls, therefore, a thorough understanding about knowledge on HPV, cervical cancer and HPV vaccination of secondary school girls and their practice on HPV vaccination is needed. Objective: The aim of this study is to investigate the knowledge of secondary school girls about human papillomavirus (HPV), cervical cancer and human papillomavirus (HPV) vaccination and their practices on HPV vaccination. Methods: A cross sectional study was conducted in two secondary schools; SMK TengkuPanglimaPerang and SMK (P) Methodist, Kuantan, Pahang, Malaysia. The total numbers of 295 secondary school girls were studied, and the data were collected through the distribution of structured questionnaires. Data analysis involved descriptive statistic and chi square test by using SPSS version 20. Results: Results revealed that there was a high level of knowledge about HPV, cervical cancer, and HPV vaccination, however low/poor practice on HPV vaccination among secondary school girls. Conclusion: Therefore, it is suggested that further study is required to focus the gap between knowledge, and practice, and examines the reasons of not receiving HPV vaccinations in the targeted group. Strategies for enhancing awareness to take HPV vaccination are also needed.